Engineering polymer solar cells: advancement in active layer thickness and morphology. Issue 28 (7th July 2021) - Gupta, Ritesh Kant; Garai, Rabindranath; Hossain, Maimur; Afroz, Mohammad Adil; Kalita, Dibashmoni; Iyer, Parameswar Krishnan
Abstract : This review consists of technological and molecular evolutions that have been developed recently to modulate the morphology and achieve a thick photoactive layer, which has taken us closer to commercialization of polymer solar cells. Abstract : Achieving high power conversion efficiency (PCE) polymer solar cells (PSCs) has been very challenging and the ultimate goal for their commercialization. Precise investigation of the active layer morphology and newer methods to process these layers has been a crucial factor to realize high PCE. There is also a rising demand for the fabrication of PSCs with a thick active layer over a large area to facilitate their commercial application. However, to achieve higher thickness it has been observed that the active layer film morphology is compromised, which in turn reduces the device performance. Many device engineering techniques have been attempted by researchers to obtain the best possible morphology for enabling better charge transport and hence improved device efficiency. Reports of achieving thick active layer PSCs along with regulation of the morphology in favour of charge transport have also appeared in the literature. This review aims to cover important device engineering techniques which have been reported in the literature for obtaining high performance PSCs by modifying the morphology and those which have been targeted to achieve thick active layers for the same. Besides including general device engineering aspects, a discussion on varying the donor (D) and acceptor (A) ratio and thermal annealing for regulating the active layer is also included. Thereafter, solvent/additive engineering and materials engineering have been discussed to understand their role in the active layer morphology and fabrication of thick film solar cells. Lastly, all the advanced device engineering methods such as solvent vapor annealing, doctor blading, and hot-casting for the fabrication of high-performance PSCs have been covered. This review will be a good tool for all researchers who are considering various device engineering methods to obtain high performance thick PSCs.